1997
DOI: 10.1046/j.1365-3083.1997.d01-88.x
|View full text |Cite
|
Sign up to set email alerts
|

Priming to Mycobacterial Antigen In Vivo Using Antigen‐Pulsed Antigen Presenting Cells Generated In Vitro is Influenced by the Dose and Presence of IL‐4 in APC Cultures

Abstract: Antigen presenting cells (APC) similar to immature dendritic cells can be generated in vitro from bone marrow precursors. The authors have compared the yield, the phenotype and the function of murine bone marrow cells cultured for 7 or 11 days in either granulocyte macrophage colony stimulating factor alone (GM BMAPC) or in combination with interleukin‐4 (GM/IL‐4 BMAPC). The results showed that GM/IL‐4 BMAPC expressed the highest levels of MHC Class 2 molecules, CD86 /B7‐2 and CD80/B7‐1 co‐stimulatory molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1

Year Published

1998
1998
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 44 publications
2
6
1
Order By: Relevance
“…The expression of these molecules is of course of fundamental importance in the presentation of antigen and the delivery of signals to T cells. Other groups have observed that, in the presence of FCS, DC cultured in the absence of IL‐4 also express suboptimal levels of MHC class II, CD40, CD80 and CD86 when compared with DC cultured in the presence of IL‐4 [7, 12–16, 18], although we did not find this to be the case in this study.…”
Section: Discussioncontrasting
confidence: 93%
See 1 more Smart Citation
“…The expression of these molecules is of course of fundamental importance in the presentation of antigen and the delivery of signals to T cells. Other groups have observed that, in the presence of FCS, DC cultured in the absence of IL‐4 also express suboptimal levels of MHC class II, CD40, CD80 and CD86 when compared with DC cultured in the presence of IL‐4 [7, 12–16, 18], although we did not find this to be the case in this study.…”
Section: Discussioncontrasting
confidence: 93%
“…Although we, in this study, did not explore the ability of DC cultured in FCS to take up antigen, previous studies have reported that DC that are generated in the presence of IL‐4 are less efficient at taking up FITC–Dextran [7, 12, 15] or mannosylated BSA [13] via the mannose receptor than DC cultured in the absence of IL‐4. It is possible that serum has an effect on the levels of mannose receptor expression, which would affect the uptake of antigens.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo naı¨ve T lymphocytes can be sensitized against bacillary antigens by antigen‐presenting cells delivering Mtb‐PPD antigens 10–14 . Peripheral blood lymphocytes from 11 tuberculin‐negative, healthy individuals were cocultured with autologous DC and 400 µg/ml Mtb‐PPD (MLC).…”
Section: Resultsmentioning
confidence: 99%
“…To address this question Mtb‐PPD‐specific T lymphocytes were generated using autologous dendritic cells (DC) loaded with bacillary antigens. As the most potent antigen‐presenting cells, 8,9 DC are capable of taking up and processing not only whole mycobacteria but also Mtb‐PPD, and are known to deliver Mtb‐PPD and other bacillary antigens to naı¨ve T lymphocytes resulting in a Th1 immune response in vivo and in vitro 10–14 . Herein we report that on re‐exposure to bacillary antigens Mtb‐PPD‐specific γδ + , αβ + CD4 + , and αβ + CD8 + T lymphocytes become reactive and apoptotic via Fas‐dependent cytolytic mechanisms in an antigen‐concentration‐dependent manner.…”
Section: Introductionmentioning
confidence: 94%
“…Antigen-presenting cell source. A modified method of Inaba et al [23], for the isolation of bone marrow precursors, was used [25]. Briefly, the bone marrow was flushed from femurs and tibias with cDMEM þ 5% FCS, the red blood cells were lysed with ammonium chloride and the remaining cells were washed four times.…”
Section: Methodsmentioning
confidence: 99%